Observational Tools Using Video Recordings of Parent-Child Feeding Interactions: A Narrative Review - Gessica D'Angeli; Martina Mesce; Luca Cerniglia; Silvia Cimino (MDPI AG, 2022)
Current research has confirmed that the quality of the caregiver-child relationship influences the child's emotional and behavioral development. Play and feeding contexts, for example, are the best contexts to observe mother-child or father-child interaction. The observation of feeding interaction establishes involvement on the part of both parties and identifies relationship characteristics. The purpose of this study is to select and describe the most frequently used observational methods during feeding interactions in the first three years of a child's life. Instruments that employ video recordings of mealtimes will be detailed to highlight the relevance that specific tools have nowadays. Finally, the SVIA (Scala di Valutazione delle Interazioni Alimentari), a technique for analyzing food interactions by observation that has also been utilized remotely, will be offered. This is intended to provide practitioners and researchers with an overview of tools while also taking into consideration the present scenario in which digital tools are increasingly being employed in health and clinical settings. Furthermore, the purpose of this paper is to review the various observational methods of the parent-child relationship to assist future practitioners and researchers in the field in making an accurate assessment of caregiver-child interaction and selecting a valid tool for the early recognition of problematic relationships and identifying the most appropriate treatment modalities.